Liana versus tree seedling responses to spatial and temporal variation in dry season severity - Sergio Estrada‐Villegas; Luke Browne; Eric Manzané‐Pinzón; Liza S. Comita (Ecosphere)
Abstract Lianas are key components of tropical forests, particularly at sites with more severe dry seasons. In contrast, trees are more abundant and speciose in wetter areas. The seasonal growth advantage (SGA) hypothesis postulates that such contrasting distributions are produced by higher liana growth relative to trees during seasonal droughts. The SGA has been investigated for larger size classes (e.g., ≥5 cm diameter at 1.3 m, dbh), but rarely for seedlings. Using eight annual censuses of >12,000 seedlings of 483 tree and liana species conducted at eight 1‐ha plots spanning a strong rainfall gradient in central Panama, we evaluated whether liana seedlings had higher growth and/or survival rates than tree seedlings at sites with stronger droughts. We also tested whether an extreme El Niño drought during the study period had a more negative effect on tree compared to liana seedlings. The absolute density of liana seedlings was similar across the rainfall gradient, ranging from 0.32 individuals/m2 (0.20–0.49, 95% credible interval [CI]) at the driest end of the gradient and 0.27 individuals/m2 (0.13–0.51 95% CI) at the wettest end of the gradient. The relative density of liana seedlings compared to tree seedlings was higher at sites with stronger dry seasons (0.27, 0.21–0.33, 95% CI), compared to wetter sites (0.12, 0.04–0.20 95% CI), due to lower tree seedling densities at drier sites. However, liana seedlings did not grow or survive better than tree seedlings in drier sites compared to wetter sites. Tree seedlings were more negatively impacted in terms of mortality by the extreme El Niño drought than liana seedlings, with an increase in annual mortality rate of 0.013 (0.003–0.025 95% CI) compared to lianas of −0.009 (−0.028 to 0.008 95% CI), but not growth. Our results indicate that lianas do not have a SGA over trees at the seedling stage. Instead, higher survival of liana versus tree seedlings during severe droughts or differences in liana versus tree fecundity or germination across the rainfall gradient likely explain why liana seedlings have higher relative densities at drier sites.